Statistical Considerations for Exercise Protocols Aimed at Measuring Trainability. Issue 1 (January 2019) - Voisin, Sarah; Jacques, Macsue; Lucia, Alejandro; Bishop, David J.; Eynon, Nir
Abstract : The individual response to exercise training is of great interest with methods that have been proposed to measure this response reviewed in this paper. However, individual training response estimates may be biased by various sources of variability present in exercise studies, and in particular by within-subject variability. We propose the use of protocols that can separate trainability from within-subject variability. Abstract : Repeated exercise interventions (for short interventions) or repeated testing during the intervention (for long interventions) should be used to partition trainability from within-subject variability.